Influence of age on haematological and biochemical blood profiles of black Bengal goats (Capra hircus) (Bangladesh Veterinarian, 2023)
The study was conducted to know the effects of age on haemato-biochemical profiles in Black Bengal (BB) goats. Fifty BB goats were equally divided into five groups: group A (control, 3 years), group B (>3 - 5 years), group C (2-